Development of the Malaysian river integrity index (MYRII) based on biological, chemical and physical multi-metrics - Ng, Keat Chuan (2020)
Malaysia is currently undergoing dramatic geohydrologic changes due to unsustainable land development activities and this threatens the integrity of freshwater resources. Considering the steady national population growth, Malaysia will need more freshwater into the future for household, recreation and industrial consumption. And yet, methodical river assessment and management is minimal as suggested by literature review. Prompted by the predicament, this study’s objective was to pioneer an assessment system that can be readily adopted to assess, monitor and drive river conservation in a wholesome manner. Literature review showed that the inclusion of biological, chemical and physical metrics is crucial for formulating a wholesome assessment system. Hence, three sets of a priori metrics were selected to form the Ichthyofaunal Quality Index (IQI; biological), Water Quality Index (WQI; chemical) and River Physical Quality Index (RPQI; physical). These indices were further normalized and integrated on equal weighting to construct a novel Malaysian River Integrity Index (MyRII). Additionally, the ecosystem service economic value of the study site was also calculated using the Market-Price-Method. To test its robustness, the MyRII protocol was field tested in four ecohydrological zones (i.e. Zone A, B, C and D) located along the Kampar River for 18 months to reveal its strengths and weaknesses. Statistical analysis functions of software IBM SPSS version 20 were applied to determine the variances, correlations and clustering patterns of metrics and indices. This was crucial as the metrics and indices were expected to detect any anomalies, noncompliances and distinguish the studied zones according to their biological, chemical and physical characteristics. Additionally, the 75%, 50% and 25% percentile thresholds were computed statistically from combined dataset of Zone A and B for establishing the “good”, “average” and “poor” rating, respectively. The resultant MyRII showed a clear trend that corresponded with different levels of river impairment. Zone A which was a reference site with minimal disturbance achieved the highest MyRII (89.69 ± 4.42), followed by zone B (62.22 ± 6.02) and zone C (50.19 ± 4.28). However, the MyRII in zone D (63.37 ± 6.90), which was a heavily disturbed wetland, did not conform to such trend. Also unveiled and recognized, however, are some limitations in IQI assessment, namely the implications of species niches, species physiology, introduced species and the lack of taxonomy expertise in Malaysia. Sporadic non-compliances of water chemistry parameter namely bio-chemical oxygen demand, turbidity, ammoniacal nitrogen and dissolved oxygen were detected by the WQI assessment. The possible natural and anthropogenic causes and implications were critically discussed as precautions for interpreting and implementing the MyRII protocol. Although this thesis deals mainly with an exemplar river in Malaysia, the core principles and approaches proposed have global relevance. The immediate issue at stake is, unless the ecological interactions between biology, chemistry and physical components are recognized and assessed in a multidisciplinary manner, only partial or deficient data are available to drive restoration and management initiatives. This research adds to the mounting body of evidence that water resource stakeholders and policymakers must look at the big picture and adopt the “balanced ecosystem” mindset when assessing and managing Malaysia's freshwater resource.